Patient-centered care and satisfaction of patients with diabetes: insights from a survey among patients at primary healthcare centers in Saudi Arabia - Nizar Alsubahi; Wim Groot; Ahmed Ali Alzahrani; Ala’eddin Ahmad; Milena Pavlova (BMC Primary Care)
Abstract Background and objective Patient-centered care (PCC) and patient satisfaction are pivotal in healthcare provision for patients with diabetes. This study investigates the link between perceived PCC and satisfaction with care among patients with diabetes in Saudi Arabia. Methods A cross-sectional study was conducted at 47 primary healthcare centers affiliated with general hospitals, including King Abdullah Medical Complex, King Abdulaziz Hospital, East Jeddah Hospital, King Fahd General Hospital, and Al Thagr General Hospital, operated by the Ministry of Health in Jeddah City, Saudi Arabia, between July and August 2023. Over 800 patients with diabetes were approached through a random sampling technique at the reception areas of these centers. These patients were directed to designated private rooms for further engagement, where they completed a face-to-face questionnaire administered by an interviewer. Data analysis was conducted using the software package SPSS version 28 and AMOS version 28. Results Of the 594 patients who participated in the study (response rate 73.4%), the results indicated that the perceived level of PCC, including physical comfort (β = 0.200, p = 0.000), continuity in care transition (β = 0.114, p = 0.031), access to care (β = 0.203, p = 0.000), information and education (β = 0.169, p = 0.001), and family and friends involvement (β = 0.082, p = 0.023), were significantly related to patient satisfaction. However, other perceived PCC components, like patient preferences (β = 0.052, p = 0.233), care coordination (β = 0.078, p = 0.123), and emotional support (β=-0.080, p = 0.066), did not appear to have a significant relationship with patient satisfaction. Income and level of education substantially impacted the perception of PCC and satisfaction with care. One notable finding was that the perceived level of PCC had a strong positive relationship with patient satisfaction (β = 0.762, p = 0.002). Conclusion This study highlights the significant positive relationship between PCC and patient satisfaction in diabetes care in Saudi Arabia. It emphasizes the need for healthcare tailored to individual needs and demographic factors. This provide advocates the broader integration of PCC principles in health systems, particularly in Saudi Arabia, to improve patient experience and satisfaction. Policymakers should integrate patient-centered care into healthcare policies to improve service quality and health outcomes.